Pengaruh Kualitas Sumberdaya Manusia Dan Implementasi Kebijakan Dinas PUPR Terhadap Pembentukan Pola Ruang Di Kecamatan Bissappu Kabupaten Bantaeng - Titin Supriyatin; Rudi Latief; Syafri Syafri (Postgraduate Bosowa University, 2021)
Penelitian ini bertujuan mengidentifikasi dan menganalisis bagaimana pengaruh kualitas sumberdaya manusia dan implementasi kebijakan Dinas PUPR Kabupaten Bantaeng secara bersama-sama terhadap pembentukan pola ruang di Kecamatan Bissappu Kabupatren Bantaeng. Metode analisis yang digunakan dalam penelitian ini yaitu pengujian data-data yang diperoleh berdasarkan data times series atau waktu ke waktu berdasarkan data yang dikumpulkan selama interval waktu lima (5) tahun. Pengujian dalam penelitian ini dilakukan dengan model korelasi. Korelasi yang digunakan antara lain metode korelasi liner sederhana kemudian untuk dilakukan pengujian korelasi berganda. Korelasi berganda yaitu metode statistika yang digunakan untuk mengetahui pola umum hubungan yang mempengaruhi antara variabel. yang diterima kemudian dianalisis manual sesuai prosedur analisis dalam penelitian. Keberhasilan penerapan implementasi kebijakan pelayanan IMB maka semakin kuat pengaruhnya terhadap pembentukan pola ruang dimana rhitung = 0,9805 lebih besar dari r tabel= 0.878 pada taraf signifikansi 5 % dimana H0 dtolak dan H1 diterima. Hasil pengujian dan perhitungan analisis korelasi terhadap Variabel peningkatan Kualitas sumberdaya manusia(pegawai)(X1) dan Implementasi Kebijakan(X2) secara bersama-sama memiliki keterhubungan sangat kuat terhadap Pembentukan Pola ruang sebesar 0.9801. Dimana jika Rhitung lebih besar dari Rtabel sebesar 0,878, pada taraf signifikansi alpha adalah 0.05, maka H0 di tolak dan H1 diterima. This study aims to identify and analyze how the influence of the quality of human resources and the implementation of the policies of the PUPR Office of Bantaeng Regency together on the formation of spatial patterns in Bissappu District, Bantaeng Regency. The analytical method used in this study is testing the data obtained based on times series data or time to time based on data collected over a five (5) year time interval. Tests in this study were conducted with the correlation model. The correlation used includes a simple linear correlation method and then multiple correlation tests are carried out. Multiple correlation is a statistical method used to determine the general pattern of relationships that affect between variables. received is then analyzed manually according to the analytical procedures in the study. Where in this study has more than one independent variable. Looking at the results of the above calculation, the influence of human resources (X1) on the formation of spatial patterns (Y) has a moderate correlation, namely 0.421 where rcount rtable = 0.878 at a significance level of alpha 0.05 then H0 is accepted and H1 is rejected. This proves that improving the quality of human resources (employees) does not have a significant relationship with the formation of spatial patterns. The results of the analysis of correlation calculations in chapter IV show that policy implementation (X2) has a very strong relationship with the formation of spatial patterns (Y). The successful implementation of the IMB service policy implementation, the stronger the influence on the formation of spatial patterns where rcount = 0.9805 is greater than rtable = 0.878 at a significance level of 5% where H0 is rejected and H1 is accepted. The results of testing and calculation of correlation analysis on the Variable of improving the quality of human resources (employees) (X1) and Policy Implementation (X2) together have a very strong relationship to the formation of spatial patterns of 0.9801. Where if Rcount is greater than Rtable of 0.878, at the alpha significance level is 0.05, then H0 is rejected and H1 is accepted